Heterotopic Pregnancy: Case Series and Review of Diagnosis and Management - Somaia Elsayed; Nadine Farah; Mary Anglim (Case Reports in Obstetrics and Gynecology, 2023)
Introduction. Heterotopic pregnancy (HP) refers to the simultaneous presence of intrauterine pregnancy (IUP) and ectopic pregnancy, which is very rare but potentially life-threatening. The spontaneous incidence of HP in the general population is 1/30,000. With the widespread use of assisted reproductive technology (ART), the incidence rises to 1/1,000. Aims and Methods. This is a prospective case series looking at the cases of heterotopic pregnancies presenting to the early pregnancy unit (EPU) in a tertiary maternity hospital, from November 2015 to November 2016. The clinical presentation, ultrasound findings, and laparoscopy findings were all documented. The incidence of HP was calculated and compared with the quoted incidence in the literature. Outcomes. Five women with HP presented to the EPU over the course of a year. The first case describes a spontaneous HP with a previous salpingostomy. The second case describes an HP following ovulation induction. The third case describes a spontaneous HP with no known risk factors. The fourth and fifth cases describe heterotopic pregnancies following in vitro fertilisation with more than one embryo. All five cases of HP underwent laparoscopy and salpingectomy with uneventful recovery. The three women who had a viable IUP had no further complications in their pregnancies. Conclusion. Early and accurate diagnosis of HP can be challenging. An early transvaginal ultrasound plays an important role in making the diagnosis in women with risk factors and following ART. A high index of suspicion is required for timely diagnosis and appropriate intervention, especially in spontaneous HP.